Overcoming Performance Anxiety - Stiplošek, Nina (Širjenje obzorij o poučevanju glasbe, 2025)
Musical performance anxiety is a common issue among young musicians and can negatively impact their confidence and performance. This chapter examines the causes of performance anxiety, which arise from a combination of biological, psychological, and environmental factors. It also presents various relaxation techniques, such as meditation, the Alexander Technique, and progressive relaxation, which can help manage anxiety. Teachers play a crucial role in addressing performance anxiety by employing strategies like performance simulation, a positive approach, thorough preparation, and breathing exercises. While additional training may be needed to support students with performance anxiety, many effective strategies can be seamlessly integrated into regular teaching practices.